Expressive writing therapy for academic stress among twelfth-grade students - Nurhasanah Nurhasanah; Osep Yasier Almunsiri; Lailatul Fadilah; Cucuk Kunang Sari (JOURNAL OF Mental Health Concerns, 2026)
Background: Grade XII students are in the transitional phase of late adolescence, making them vulnerable to severe psychosocial pressure. A dense curriculum, final exam preparation, and intense competition for university entrance selection trigger academic stress. Expressive Writing Therapy (EWT) is an effective independent complementary nursing intervention for managing emotional pressure, utilizing expressive writing to release mental burdens and facilitate cognitive restructuring. Purpose: To identify the effect of expressive writing therapy on reducing academic stress levels in grade xii students. Method: A quantitative research method with a quasi-experimental approach using a one-group pretest-posttest design. Purposive sampling was used to select a sample of 36 Grade XII students. The research instrument was an adapted version of the Educational Stress Scale for Adolescents (ESSA) questionnaire. Bivariate data analysis was performed using the non-parametric Wilcoxon Signed-Rank Test. Results: Statistical analysis showed that the mean academic stress score before the intervention (pre-test) was 53.83, which significantly decreased to 35.56 after the intervention (post-test), yielding a p-value of 0.00. Conclusion: There is a meaningful and significant effect of Expressive Writing Therapy on reducing academic stress levels among Grade XII students.  Keywords: Academic Stress; Expressive Writing Therapy; Late Adolescence.